A Multidirectional Perspective for Novel Functional Products: In vitro Pharmacological Activities and In silico Studies on Ononis natrix subsp. hispanica - Yerlikaya, Serife; Zengin, Gokhan; Mollica, Adriano; Baloglu, Mehmet C.; Celik Altunoglu, Yasemin; Aktumsek, Abdurrahman (Frontiers in Pharmacology, 2017)
The genus Ononis has important value as traditional drugs and foods. In the present work, we aimed to assess the chemical profiles and biological effects of Ononis natrix subsp. hispanica extracts (ethyl acetate, methanol and water). For chemical profile, total and individual phenolic components were detected. For biological effects, antioxidant (DPPH, ABTS, CUPRAC, FRAP, phosphomolybdenum and metal chelating assays), enzyme inhibitory (against cholinesterase, tyrosinase, α-amylase and α-glucosidase), antimicrobial, DNA protection and cytotoxic abilities were tested. The predominant phenolics were apigenin, luteolin and quercetin in the tested extracts. Generally, the ethyl acetate and methanol extracts were noted as the most active in the antioxidant and enzyme inhibitory assays. Water extract with different concentrations indicated high level of DNA protection activity. Methanol and ethyl acetate extracts showed antibacterial effect against to Staphylococcus aureus and Staphylococcus epidermidis strains. The cytotoxic effects of O. natrix subsp. hispanica extracts on the survival of HeLa and PC3 cells were determined by MTT cell viability assay. Water and methanol extracts caused initiation of apoptosis for PC3 cell line. Furthermore, molecular docking was performed to better understand interactions between dominant phenolic compounds and selected enzymes. Our results clearly indicate that O. natrix subsp. hispanica could be considered a potential candidate for designing novel pharmaceuticals, cosmeceuticals and nutraceuticals.